Monitoring of vancomycin in human plasma via portable microchip electrophoresis with contactless conductivity detector and multi-stacking strategy - Chong, Kah Chun, 1992-, author; See, Hong Heng, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Falsafah (Kimia)) - Universiti Teknologi Malaysia, 2017